Stem Cell-Mediated Angiogenesis in Tissue Engineering Constructs - Kiaie, Nasim; Aghdam, Rouhollah M.; Tafti, Seyed H. Ahmadi; Gorabi, Armita M. (Current Stem Cell Research & Therapy, 2019)
Angiogenesis has always been a concern in the field of tissue engineering. Poor vascularization of engineered constructs is a problem for the clinical success of these structures. Among the various methods employed to induce angiogenesis, stem cells provide a promising tool for the future. The present review aims to present the application of stem cells in the induction of angiogenesis. Additionally, it summarizes recent advancements in stem cell-mediated angiogenesis of different tissue engineering constructs.
Keywords: stem cell